46. EVALUATION OF SATISFACTION OF OUTPATIENT AT TAM ANH HANOI GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: The study was conducted to evaluate the satisfaction of patients coming for medical examination and treatment at the outpatient departments of Tam Anh Hanoi General Hospital in 2024 as well as analyze several related factors.Research objects and methods: Use a self-completed questionnaire using a 5-level Likert scale to collect data from 415 patients and their families (for pediatric patients) who came for outpatient examination at Tam Anh General Hospital, Hanoi.Results: 95.7% of study subjects were satisfied with the quality of outpatient medical examination and treatment at Tam Anh General Hospital. The satisfaction rate for some services is high such as transparency in information and medical examination and treatment procedures: average score 4.25 ± 0.51; behavioral attitude and professional capacity: average score 4.24 ± 0.46; facilities to serve patients: average score 4.24 ± 0.43. On the contrary, the patient satisfaction rate is lower with some criteria such as: medical examination and treatment costs with an average score of 4.14 ± 0.44; waiting time for testing and imaging services with an average score of 4.20 ± 0.59.Conclusion: The majority of patients are satisfied when coming for outpatient medical examination and treatment at Tam Anh General Hospital in Hanoi, accounting for more than 90% of the survey subjects. However, there still needs to be measures to improve service quality and customer satisfaction when coming for same-day examination and treatment.
Keywords: Outpatient services, patient satisfaction, Tam Anh General Hospital.